EFFECT OF CELL-CYCLE SYNCHRONIZATION ON THE ACCURACY OF MURINE AND BOVINE EMBRYO SEX DETERMINATION - Delima, VFMH; Debem, A. R.; Jorge, W.; Moreirafilho, C. A. (Butterworth-heinemann, 1994)
Different cell cycle synchronization methods were used to increase the mitotic index and accuracy of sex determination in murine and bovine embryos. For sexing purposes, colchicine treatment for 2, 4, 6 and 8 h and the FdU-thymidine-colchicine combination were tested in murine embryos. The best results were obtained with colchicine treatment for 8 h (96.88% accuracy) and with FdU-thymidine-colchicine (97.22% accuracy). Mitotic indexes differed significantly between the 2 treatments (21.71% for colchicine and 32.95% for FdU-thymidine-colchicine). For sex identification of murine and bovine demi-embryos, both treatments were demonstrated to be equally effective (nearly 90%). The mitotic index for the FdU-treated murine demi-embryos (19.04%) was higher than the one obtained for the 8-h colchicine treatment (15.62%).
Keywords: EMBRYO; SEXING; COLCHICINE; FLUORDEOXYURIDINE